A BIBLIOMETRIC STUDY OF SPACECRAFT RESEARCH LITERATURE - Loganayaki, R.; Amudha , G.; Yesudoss, P. (International Journal of Psychosocial Rehabilitation, 2020)
This study presents the Bibliometric analysis on geographical distributions of global spacecraft literature research outputs. The study covers a period of 15 years from the year 2000 to 2014. It deals with countrywise annual productivity and their Ratio of Growth (RoG), Annual Average Growth Rate (AAGR), Activity Index (AI) of countries, Countrywise bibliographic form of publications, and Relative Quality Index (AI). There are 258861 publications during the study period. United States of America has contributed 27.94% of the total publications. Activity Index of China and India shows tremendous increase in research and development activities in the field of study. The researchers mostly prefer the journal article as the medium of communication for their research productivity. United States of America, Germany, United Kingdom, France and Canada has contributed more number of quality publications to the global spacecrafts literature.